Blood loss and transfusion risk in intramedullary nailing for subtrochanteric fractures. Issue 1 (22nd August 2022) - Panteli, Michalis; Vun, James S. H.; Ahmadi, Milad; West, Robert M.; Howard, Anthony J.; Chloros, George; Pountos, Ippokratis; Giannoudis, Peter V.
Abstract: Background: The incidence of hip fractures and subtrochanteric fractures in particular is increasing, along with the globally expanding aging population. Intramedullary nailing remains the 'gold standard' of their treatment. Blood loss can be a result of the original trauma, but also secondary to the subsequent surgical insult, especially during the reaming of the intramedullary canal. Objectives: The aim of our study was to report on the blood loss and incidence of blood transfusion in patients presenting with a subtrochanteric fracture treated with intramedullary nailing. Most importantly, we aim to identify factors associated with the need for transfusion within the first 48 h post‐operatively. Methods: Following institutional board approval, 431 consecutive patients (131 males; age: 79.03 years old, SD 13.68 years) presenting in a Level 1 Trauma Centre with a subtrochanteric fracture treated with an intramedullary nail were retrospectively identified, over an 8‐year period. Exclusion criteria included patients with high energy injuries, pathological fractures, primary operations at other institutions and patients lost to follow‐up. To identify risk factors leading to increased risk of transfusion, we first compared patients requiring intra‐operative transfusion or transfusion during the first 48 h post‐operatively against those who did not require transfusion. This was then followed by multivariate regression analysis adjusted for confounding factors to identify the most important risk factors associated with need for transfusion within the first 48 h post‐operatively. Results: Incidence of blood transfusion was 6.0% pre‐operatively, compared to 62.7% post‐operatively. A total of 230 patients (52.3%) required either intra‐operative transfusion or transfusion during the first 48 h following surgery. Patients having a transfusion within the first 48 h post‐operatively had a higher incidence of escalation in their care ( p  = 0.050), LOS ( p  = 0.015), 30‐day ( p  = 0.033) and one‐year mortality ( p  = 0.004). Multivariate regression analysis adjusted for confounding factors identified that the most important association of a need for transfusion within the first 48 post‐operative hours was a pre‐operative Hb <100 g/L (OR 6.64); a nail/canal ratio <70% (OR 3.92), followed by need for open reduction (OR 2.66). Fracture involving the lesser trochanter was also implicated with an increased risk (OR 2.08). Additionally, pre‐operative moderate/severe renal impairment (OR 4.56), as well as hypoalbuminaemia on admission (OR 2.10) were biochemical predictors of an increased risk of transfusion. Most importantly, the need for transfusion was associated with an increase in 30‐day mortality (OR 12.07). Conclusion: Several patient, fracture and surgery related factors are implicated with an increased risk for transfusion within the first 48‐h post‐operatively. Early identification, and where possible correction of these factors can potentially reduce blood loss and risk of transfusion, along with all the associated sequelae and mortality risk. Level of Evidence: III.